2021
DOI: 10.3389/fphys.2021.640237
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Exercise Training and Vitamin D Supplementation on Mitochondrial Function of Cardiac Tissue, Antioxidant Capacity, and Tumor Growth in Breast Cancer in Bearing-4T1 Mice

Abstract: Both regular exercise training and vitamin D consumption are beneficial for patients with cancer. The study investigated the effects of interval exercise training (IET) or/and vitamin D supplementation on the gene expression involved in mitochondrial function of heart tissue, tumor size, and total antioxidant capacity (TAC) in breast cancer (BC) model mice. We assigned random 40 female NMRI mice to five equal groups (n = 8); the healthy control group (H.C), cancer control group (Ca.C), cancer with the vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…The addition of vitamin D to human skeletal muscle cells was reported to enhance skeletal-muscle mitochondrial fusion and inhibit mitochondrial fission (12). In addition, in cardiac tissue in mice, vitamin D treatment significantly enhanced the mRNA expressions of peroxisome proliferator-activated receptor-gamma coactivator (PGC)-1a (a marker of mitochondrial biogenesis) and dynamin-related protein (DRP)1 (a marker of mitochondrial fission) (13). Although the effects of vitamin D administration on skeletal muscle have been reported, the effects of vitamin D deficiency on skeletal-muscle mitochondrial biogenesis, dynamics, and quality control have not been clarified.…”
mentioning
confidence: 99%
“…The addition of vitamin D to human skeletal muscle cells was reported to enhance skeletal-muscle mitochondrial fusion and inhibit mitochondrial fission (12). In addition, in cardiac tissue in mice, vitamin D treatment significantly enhanced the mRNA expressions of peroxisome proliferator-activated receptor-gamma coactivator (PGC)-1a (a marker of mitochondrial biogenesis) and dynamin-related protein (DRP)1 (a marker of mitochondrial fission) (13). Although the effects of vitamin D administration on skeletal muscle have been reported, the effects of vitamin D deficiency on skeletal-muscle mitochondrial biogenesis, dynamics, and quality control have not been clarified.…”
mentioning
confidence: 99%
“…A further notable result in the current study was that ingestion of sturgeon fillets increased the amount of intake in food and the blood concentration of 25OHD. Antioxidant and anti‐inflammatory effects of vitamin D have been shown in previous reports 29–38 . Vitamin D deficiency is defined as 25OHD <20 ng/mL (50 nmol/L) and vitamin D insufficiency as 25OHD of 21–29 ng/mL (525–725 nmol/L) 39 .…”
Section: Discussionmentioning
confidence: 93%
“…Antioxidant and anti-inflammatory effects of vitamin D have been shown in previous reports. [29][30][31][32][33][34][35][36][37][38] Vitamin D deficiency is defined as 25OHD <20 ng/mL (50 nmol/L) and vitamin D insufficiency as 25OHD of 21-29 ng/mL (525-725 nmol/L). 39 However, seven of the nine runners had a blood 25OHD level of 29 ng/mL or less.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the MAPK1 signaling pathway has known to be crucial in the transcription and translation of biomarkers of inflammation and oxidative stress [ 69 , 70 ]. Jafari et al (2021) reported that Vit D supplementation along with exercise modulates antioxidant defense and the expression of antioxidant genes [ 71 ]. Vit D is also considered an antioxidant that might cause the expression of several genes involved in the antioxidant defense system, including GPX, GSH, CAT, SOD, and the suppression of NADPH oxidase [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%